Markers of restenosis after percutaneous transluminal balloon angioplasty in patients with critical limb ischemia - Sobolevskaya, Elvira V.; Shumkov, Oleg A.; Smagin, Mikhail A.; Guskov, Andrey E.; Malysheva, Alexandra V.; Atuchin, Victor V.; Nimaev, Vadim V. (International journal of molecular sciences)
Among cardiovascular diseases, chronic obliterating lesions of the arteries of lower extremities, which are one of the important problems of modern healthcare, are distinguished. In most cases, the cause of damage to the arteries of lower extremities is atherosclerosis. The most severe form is chronic ischemia, characterized by pain at rest and ischemic ulcers, ultimately increasing the risk of limb loss and cardiovascular mortality. Therefore, patients with critical limb ischemia need limb revascularization. Percutaneous transluminal balloon angioplasty is one of the least invasive and safe approaches, with advantages for patients with comorbidities. However, after this procedure, restenosis is still possible. Early detection of changes in the composition of some molecules as markers of restenosis will help screen patients at the risk of restenosis, as well as find ways to apply efforts for further directions of inhibition of this process. The purpose of this review is to provide the most important and up-to-date information on the mechanisms of restenosis development, as well as possible predictors of their occurrence. The information collected in this publication may be useful in predicting outcomes after surgical treatment and will also find new ways for the target implication to the mechanisms of development of restenosis and atherosclerosis.